Seasonal distribution, movements and taxonomic status of blue whales (Balaenoptera musculus) in the northern Indian Ocean - Andersen, R. Charles; Branch, Trevor A.; Alagiyawadu, Anoma; Baldwin, Robert; Marsac, Francis (J. Cetacean Res. Manage., 2023)
There is a distinct population of blue whales, Balaenoptera musculus, in the northern Indian Ocean. The taxonomic status of these animals has long been uncertain, with debate over whether this population represents a distinct subspecies, and if so which name should apply. They have most frequently been assigned to B. musculus brevicauda, but are currently considered to be B. m. indica. The movements of these blue whales within the northern Indian Ocean are poorly understood. This paper reviews catches (n = 1,288), sightings (n = 448, with a minimum of 783 animals), strandings (n = 64) and acoustic detections (n = 6 locations); uses ocean colour data to estimate seasonality of primary productivity in different areas of the northern Indian Ocean; and develops a migration hypothesis. It is suggested that most of these whales feed in the Arabian Sea off the coasts of Somalia and the Arabian peninsula during the period of intense upwelling associated with the southwest monsoon (from about May to October). At the same time some blue whales also feed in the area of upwelling off the southwest coast of India and west coast of Sri Lanka. When the southwest monsoon dies down in about October–November these upwellings cease. The blue whales then disperse more widely to eke out the leaner months of the northeast monsoon (during about December to March) in other localised areas with seasonally high productivity. These include the east coast of Sri Lanka, the waters west of the Maldives, the vicinity of the Indus Canyon (at least historically), and some parts of the southern Indian Ocean. The data are consistent with the hypothesis that at least some of the blue whales that feed off the east coast of Sri Lanka in the northeast monsoon also feed in the Arabian Sea during the southwest monsoon. These whales appear to migrate eastwards past the north of Maldives and south of Sri Lanka in about December–January, returning westwards in about April–May